2016
DOI: 10.1515/hmbci-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 – a key player in cardiovascular disorders?

Abstract: Fibroblast growth factor 21 (FGF21) is a newly discovered adipokine, synthesized by several organs, mostly by the liver, which was introduced as a potent metabolic regulator and insulin-sensitizing factor. Numerous animal studies have demonstrated that FGF21 improves glucose and lipids metabolism and exerts anti-inflammatory effects. However, data obtained from human studies have shown contradictory results, in which circulating FGF21 levels were often elevated in obesity, dyslipidemia, type 2 diabetes (DM2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…FGF-21 is produced by muscle fibers, and studies have shown that it improves skeletal muscle function [ 19 ], although FGF-21 is also produced by cardiomyocytes in a response to various stress factors [ 11 ]. Based on research data on the cardioprotective effect of this cardiomyokine, it can be hypothesized that FGF-21 may play a clinical role in inhibiting the pathogenesis of AS [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF-21 is produced by muscle fibers, and studies have shown that it improves skeletal muscle function [ 19 ], although FGF-21 is also produced by cardiomyocytes in a response to various stress factors [ 11 ]. Based on research data on the cardioprotective effect of this cardiomyokine, it can be hypothesized that FGF-21 may play a clinical role in inhibiting the pathogenesis of AS [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…FGF-21 exerts cardioprotective effects, e.g., against cardiac hypertrophy and cardiac inflammation [ 11 ]. Data suggest that the blood levels of FGF-21 are associated with increased cardiovascular risk [ 12 ]. Our previous study found that circulating concentrations of FGF-21 have also been increased in AS patients without coronary and peripheral atherosclerosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblast growth factor 21 (FGF21) is mainly produced and secreted by the liver and adipose tissue, which acts as an endocrine-like cytokine in glucose, lipid and energy metabolism [ 1 ]. Recent studies have also revealed that circulating FGF21 levels are elevated in several metabolic abnormalities [ 2 , 3 ]. In addition, it also increases progressively as renal function declines [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies confirm that growth differentiation factor 15 (GDF-15), angiopoietin-2 (Ang-2), vascular endothelial growth factor (VEGF), and fibroblast growth factor 2 (FGF-2) are implicated in inflammation and angiogenesis [13][14][15]. Anti-inflammatory growth factor fibroblast growth factor 21 (FGF21) is also of clinical importance [16,17]. Metalloproteinase (MMP)-9 is involved in the pathogenesis of AS [18,19].…”
Section: Introductionmentioning
confidence: 99%